Transfer of Airport PAS Administration Procedures from Offline to Online at the Makassar Regional V Airport Authority Office - Ernawati Ernawati; Kifni Yudianto (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
Airport Public Address System (PAS) Card is a limited area entry permit card in the Airport area. Airport PAS is issued by the Directorate General of Civil Aviation. In order to improve security at airports, Minister of Transportation Regulation Number PM 167 of 2015 has been stipulated which is an amendment to Minister of Transportation Regulation Number PM 33 of 2015 concerning Access Control to Limited Security Areas at Airports. In it there are several articles that regulate airport security areas, control of entrances to airports and administrative sanctions for violating airport security regulations. To find out the form of transition of airport pass administration procedures from offline to online at the Makassar Region V Airport Authority Office? This research is a qualitative research with a comparative descriptive type of research that uses data collection methodologies with literature studies, observations and interviews. Sugiyono (2018), explains the notion of a qualitative research method is a research method that is based on the philosophy of postpositivism, used to research on natural object conditions, (as opposed to experiments) where the researcher is the key instrument, data collection techniques are carried out by triangulation (combined ), data analysis is inductive/qualitative in nature, and the results of qualitative research emphasize the meaning of generalizations. Comparative descriptive qualitative research in this study is used to describe and analyze the transition of airport pass administration procedures from offline to online at the Makassar Region V Airport Authority Office from the side of officers and applicants.